Pengabdian Mahasiswa dalam Membangun Fondasi Moderasi Beragama Sejak Usia Dini melalui Kegiatan Baca Tulis Al-Qur’an - Rani Maharani; Puji Rahayu; Selly Marita (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study departs from the urgency of early childhood religious education as the foundation for shaping religious and moderate character. The lack of Qur’an learning facilities and qualified teachers in Karang Mulya Village has hindered children aged 6–10 years in mastering Qur’anic literacy skills, even though this stage is considered a golden period of cognitive, affective, and psychomotor development. To address this issue, the research employed a qualitative descriptive method combined with a Project-Based Learning (PjBL) approach, which allowed the teaching process to be linked with practical and contextual activities. Data were collected through direct observation, structured interviews with parents and teachers, and careful documentation of student progress. The analysis was carried out through systematic steps of data reduction, presentation, and conclusion drawing. The findings reveal significant improvements in children’s ability to recognize, read, and write hijaiyah letters, although variations remain, particularly in creativity and independence. Furthermore, Qur’anic literacy activities meaningfully contributed to strengthening the understanding of religious moderation values, such as national commitment, tolerance, anti-violence, and acceptance of local culture. In conclusion, student service activities through Qur’anic literacy not only enhanced technical skills but also functioned as an effective medium for building religious moderation foundations from an early age.